2020
DOI: 10.1136/jitc-2019-000334
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of immune score in nasopharyngeal carcinoma using digital pathology

Abstract: BackgroundTumor-infiltrating lymphocytes have been reported as prognostic markers in tumors. We aimed to assess the prognostic value of total T cell (CD3+) density, cytotoxic T cell (CD8+) density and memory T cell (CD45RO+) density in patients with nasopharyngeal carcinoma (NPC).MethodsThe expression of CD3, CD8 and CD45RO was detected by immunohistochemistry in the training (n=221) and validation cohorts (n=115). The densities of these three markers were quantified by digital pathology both in the tumor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…However, in subgroup analysis, CD8+ cells infiltrated in the intratumoral site showed significantly improved OS (HR = 0.31; 95%CI = 0.16-0.62; P = 0.001) ( Figure 6 ). Because only one study, Wang et al , 20 reported on the association of CD8+ stromal TILs with OS, we did not perform meta-analysis on this subgroup.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in subgroup analysis, CD8+ cells infiltrated in the intratumoral site showed significantly improved OS (HR = 0.31; 95%CI = 0.16-0.62; P = 0.001) ( Figure 6 ). Because only one study, Wang et al , 20 reported on the association of CD8+ stromal TILs with OS, we did not perform meta-analysis on this subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies 5,[18][19][20][21][22][23][24][25][26][27][28][29][30] were pooled and evaluated for analysis of TILs lymphocytes for OS and DFS in NPC patients. Wang et al 24 have analyzed a large cohort and validated it with an independent cohort focusing on the total intensity of TILs, however most the rest of the studies focused on a set of phenotypic subtypes of immune cells (including CD3, CD4, CD8, regulatory T cells and macrophages).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Although limited to few studies, an association between high tumor CD8 + T-cell density and a better distant metastasis free-survival was already observed in solid tumors from different primary sites including breast [ 46 ], colon [ 47 ] or soft tissues [ 48 ]. Among head and neck malignancies, evidence derived from the analysis of nasopharyngeal carcinoma [ 49 ], hypopharyngeal carcinoma [ 50 , 51 ] or from carcinomas of mixed primary sites [ 52 ] further support this finding. For OSCC, the association of CD8 + T-cell infiltration and distant failure still needs to be better defined [ 53 ]; however, indirect but still limited findings [ 52 ], support their protective role.…”
Section: Discussionmentioning
confidence: 96%
“…On the basis of the multivariate COX regression model, each gene in the model is listed on a flat diagram by using a scaled line segment according to a certain scale. Then, each gene is scored and the scores of all genes are added to obtain a total score, which is used to predict the survival and prognosis of CRC patients [ 23 ]. The nomogram is drawn using the "rms" package of R software.…”
Section: Methodsmentioning
confidence: 99%